(untitled) (Revista Brasileira Multidisciplinar, 2011)
This study aimed at verifying the education professionals’ perception about the performance of school psychologists. To attain this goal, 24 education professionals were interviewed, being 19 educators and five school psychologists from 11 private and public schools of two cities of São Paulo state. Based on descriptions about the psychologists’ performance found in the literature, it is possible to compare them to the school psychologists’ performance and to the education professionals’ perception. From the data obtained, it was verified that the participants had knowledge, even though in a general perspective, about the performance area and considered important the service of those professionals to the school as an institution. However, it was noticed the difference of perception between the performances reported by the psychologists and these professionals’ performance described by the other education professionals interviewed, seeming to generate dissatisfaction and possible conflicts. Therefore, it is necessary that the psychologist attributions become clearer and widespread so their interventions could match educators’ expectations, provide satisfying results and be more frequently included in school institutions.